Qurʾanic Scholarly Authority Within Pesantren Networks in Indonesia: A Genealogical Reading of the Sanad of KH Munawwar Sidayu, Gresik - Hidayati, Nurul (Institut Agama Islam Negeri (IAIN) Keiri, 2025)
This study examines the formation of scholarly authority within the network of tahfiz pesantren through the Qur’anic sanad of KH Munawwar Sidayu in Gresik, which plays a pivotal role in preserving the tahfiz tradition. The research focuses on mapping the socio-intellectual and genealogical dynamics of the pesantren, as well as the interplay between knowledge, power, and epistemic legitimacy in a local context that has received limited academic attention. A qualitative approach with a genealogical method, enriched by the social history of pesantren, was employed. Data were collected through in-depth interviews with caretakers, teachers, and students; participatory observation; and examination of pesantren archives, sanad documents, and historical literature. Interpretative-genealogical analysis, grounded in Michel Foucault’s theory of power/knowledge, revealed the mechanisms of authority distribution and knowledge legitimization. Findings indicate that the sanad network, kinship relations among kyai, and collaboration with alumni and community institutions create a structured and sustainable scholarly authority system. The sanad serves as a conduit for epistemic and moral legitimacy, familial ties reinforce socio-intellectual continuity, and alumni act as agents of knowledge dissemination. Engagement with governmental and societal institutions extends the pesantren’s influence, positioning it as both a center for knowledge production and reinforcement of Qur’anic tradition. This study contributes a genealogical analytical model of tahfiz pesantren networks, enriching scholarship on intellectual networks and the legitimacy of Qur’anic knowledge transmission in Indonesia.